The Creation of Thap Wila Roengsamran ( The Feline Suite ) - กอผจญ, ชนะชัย; พรประสิทธิ์, ขำคม (Journal of Fine and Applied Arts Khon Kaen University, 2018)
The objectives of this research are: to study the history, origin, beliefs as well as the general characteristics and behaviours of feline in general and the five existing types of Thai feline in particular in order to create a new music composition; to study the musical form of the Phleng Thap (suite) genre of the classical Thai music; to study the classical Thai melodies relating to various animals and their contexts; and to integrate the acquired knowledge into the composition of Thap Wila Roengsamran (the feline Suite), which reflects the characteristics of the five existing types of Thai cats. The research employed a qualitative research methodology of interviewing seven authorities on Thai cats and classical Thai music. The research findings were analysed and presented as a descriptive analysis. The research findings include the composition of the Cat’s Suite describing the unique characteristics of the five existing types of Thai cats and data from the survey and study of historical evidences relating to Thai cats from different sources of information and textbooks. These data were used in the creative composition of the Cat’s Suite which is based on the musical form of the Phleng Thap genre of the classical Thai music. The resulting Cat’s Suite composition addresses the valuable cultural identity which are unique to Thai cats. The research findings can contribute to the study and development of the body of knowledge on Thai cats, the preservation of Thai art and culture, and the conservation of Thai cats.